Reconstructing a Model for the Internalization of Islamic Educational Philosophy Values in Islamic Elementary Schools - Siti Mardliyah; Fenia Marliana; Yulida Fauziyah; Andewi Suhartini (Jurnal Paedagogy, 2026)
This study investigates the internalization of Islamic educational philosophy values into the daily behavior of students in Islamic elementary schools, focusing on the gap between formal teaching and reflective internalization. Employing an interpretive phenomenological approach, this qualitative inquiry explores the lived experiences of school principals, educators, students, and parents across selected institutions in Bandung, Indonesia. Data were gathered through in-depth, semi-structured interviews and prolonged field observations, and subsequently analyzed using Interpretative Phenomenological Analysis (IPA) to uncover emerging themes and shared meanings. The results indicate that although values such as monotheism, adab (manners), and amanah (trustworthiness) have been integrated into the curriculum, their internalization often stalls at a superficial level. To address this, this study proposes an operational framework that emphasizes reflective pedagogy, authentic role models, and ecosystem synergy between school and family environments. These empirical insights offer a strategic, localized contribution to refining the implementation and sustainability of national values-based character education policies in developing countries.